Social isolation disrupts hippocampal neurogenesis in young non-human primates - Cinini, Simone M.; Barnabe, Gabriela F.; Galvao-Coelho, Nicole; Medeiros, Magda A.; Perez-Mendes, Patricia; Sousa, Maria B.; Covolan, Luciene; Mello, Luiz E. (Frontiers in Neuroscience, 2014)
Social relationships are crucial for the development and maintenance of normal behavior in non-human primates. Animals that are raised in isolation develop abnormal patterns of behavior that persist even when they are later reunited with their parents. In rodents, social isolation is a stressful event and is associated with a decrease in hippocampal neurogenesis but considerably less is known about the effects of social isolation in non-human primates during the transition from adolescence to adulthood. To investigate how social isolation affects young marmosets, these were isolated from other members of the colony for one or three weeks and evaluated for alterations in their behavior and hippocampal cell proliferation. We found that anxiety-related behaviors like scent-marking and locomotor activity increased after social isolation when compared to baseline levels. In agreement, grooming - an indicative of attenuation of tension - was reduced among isolated marmosets. These results were consistent with increased cortisol levels after one and three weeks of isolation. After social isolation (one or three weeks), reduced proliferation of neural cells in the subgranular zone of dentate granule cell layer was identified and a smaller proportion of BrdU-positive cells underwent neuronal fate (doublecortin labeling). Our data is consistent with the notion that social deprivation during the transition from adolescence to adulthood leads to stress and produces anxiety-like behaviors that in turn might affect neurogenesis and contribute to the deleterious consequences of prolonged stressful conditions.